Innovation in the management of sludge generated in domestic waste water treatment plants in Lima – Peru - Espinoza Eche, José Jorge (2021)
In the 7 domestic wastewater treatment plants evaluated, located in different districts of Metropolitan Lima, 2537.85 Tn / day of sludge with high moisture content are generated, becoming a problem given that the spaces for its confinement are scarce. To evaluate its transformation into an input, the sludge was physically-chemically and biologically characterized, which was done twice, and the results were compared with the maximum permissible limits established in the Peruvian, Mexican and Environmental Protection Agency regulations. In order to quantify its nutritional potential, the percentage contents of pH, organic matter, nitrogen, phosphorus and potassium were determined, which were compared with the quality results of the compost produced at the Pampamarca Chico-Carhuaz Plant. The results showed excess concentrations of Cadmium, Zinc and Thermotolerant Coliforms, in the sludge generated in the Huascar, J.C. Tello and San Juan. Regarding nutritional content, they all have high concentrations of Nitrogen and Organic Matter, and an acceptable pH. To determine the demand for use for agricultural or energy purposes, surveys were carried out, obtaining the results that: for the first, there is a potential requirement; for the second, it is necessary to apply strategies to offer it. Converting the sludge into an input requires financial resources that can be obtained by innovating the current management.